The Black Sea region in the Soviet history textbooks: features of interpretation - Казанков, Роман; Іванов, Станіслав (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2020)
Purpose. The primary goal of the paper is to disclose the process of formation and to outline the essential features of the Black Sea region within the Soviet school history textbooks. Methods. The Soviet school history textbooks’ content analysis has been put as a primary research tool to achieve the paper’s aims. Textbooks for primary and secondary school have been analyzed. Results. The postwar period has been characterized by the partial modifications of the Soviet historiography and the forming of new supranational entity – “Soviet people”. In this context the multiethnic region with the interaction between different ethnic entities’ representatives had became the research agenda. This led to increasing significance of conceptualization/reconceptualization of the Black Sea region. The complex study of the Soviet school history textbooks would allow forming the representation of the prevailing approaches toward the Black Sea region. Soviet school history textbooks’ content has already been investigated in a whole bulk of papers. However, the Black Sea region’s interpretation is still being vacant. Scholars try to disclose different issues using the textbooks’ content such as historical memory, crucial events (wars, revolutions), forming the national identity and the like (Klymenko L., Janmaat J., Gaworek N., etc). A few relevant patterns can be found within the papers generalizing the process of Soviet textbooks creating (Teleguz I.), outlining the textbooks’ significance for historical study, bringing up the new generations (Fuks A., Ogonovskaya I., etc). The paper presents the results of complex research of the Black Sea region issues within the Soviet historiography. The postwar shift in official historiography canon toward the people’s friendship and strengthening the Russians’ influence in historical development has led to modifications of the Black Sea region’s image. Textbook authors have put the stress to the common efforts of Ukrainian and Russian population in the “winning back” or “liberation” of the southern steppes from the hostile neighbors. Unanimously accepted the region’s territorial limits and endorsement of Cossacks colonization of the steppes are the main shared features of the Soviet history textbooks. The colossal significance for the trade development and border protection issues has been accentuated by the vast majority of textbook authors. Conclusions. The complex study of Soviet school history textbooks has made it feasible to circumscribe the essential features of the region’s image and to conclude the marginality of the Black Sea region within the Soviet historiography.